Identification Lithology of Land Movement Zone using the Schlumberger Configuration Geoelectric Method in Samigaluh Distric Kulon Progo - Septiana, Rena; Niyartama, Thaqibul Fikri; Wibowo, Nugroho Budi (Universitas Negeri Malang, 2024)
Samigaluh Subdistrict in Kulon Progo Regency, Yogyakarta, is prone to landslides. The objective of this study is to determine the subsurface lithology in the land movement zone. The research was conducted using the Schlumberger configuration geoelectric method. Measurements were carried out deploying six lines with line lengths ranging from 100 to 150 m. The results identified a vertical distribution of subsurface rock resistivity values to a depth of 74.05 m with a value of 0.06-13749.51 Ωm. The lithology consists of soil (14.18-361.23 Ωm), clay (0.06-42.73 Ωm), sandstone (0.35-123.44 Ωm), conglomerate (1372.7-10168.66 Ωm), and andesite 13749.51 Ωm. Damage to buildings and roads were found around the formation boundary where the damage is located in the Kebobutak formation.